Pengertian dan Hakikat Kebudayaan Islam - Viona Miftahuljannah; Haidar Daulay (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic culture is the result of human creativity, feeling, and will based on Islamic values as a guideline for life. This culture reflects human efforts to practice Islamic teachings in various aspects of life, including art, science, politics, economics, and social relations. The essence of Islamic culture lies in its integration with the teachings of revelation and noble morals sourced from the Qur'an and Hadith. Islamic culture is not only spiritual, but also includes worldly aspects that remain in line with the principles of monotheism. Therefore, this study aims to determine the meaning and essence of Islamic culture and this research method uses the library research method.